Index and localisation in sign language: interface requirement in search of features - Sinha, Samar (Nepalese Linguistics, 2019)
This paper analyses INDEX and LOCALISATION as interface requirements owing to different S-M system that creates differences in terms of their features. It aims to provide an account of the structure building feature(s) associated with various instances of the phenomena in Indian Sign Language. The corpus is collected through fieldwork with the Deaf Associations, schools, and communities in India. The methodology employed is deductive following Branson & Miller (1997) and Mathur (2000) (see Sinha 2008 for details). This paper argues that INDEX and LOCALISATION are associated with D head with dfeatures, and provides the ground from which cross-linguistic and cross-modality studies as well as investigations on universal set of features and their values can proceed.